Occurrence of human astrovirus associated with gastroenteritis among Congolese children in Brazzaville, Republic of Congo. (June 2020) - Nguekeng Tsague, Boris; Mikounou Louya, Vivaldie; Ntoumi, Francine; Adedoja, Ayodele; Vouvoungui, Christevy Jeannhey; Peko, Simon Marie; Abena, Ange Antoine
Highlights: Overall, 10% of acute gastroenteritis cases were caused by astrovirus. The mean age of cases positive for astrovirus was 12.41 ± 6.21 months. Infection with astrovirus was higher in the dry season. Higher socio-economic status was found to be associated with protection against infection. Abstract: Introduction: Acute viral gastroenteritis is a major public health concern, especially among children younger than 5 years of age. The aim of this study was to determine the occurrence of human astrovirus infection in children with acute gastroenteritis. Methods: Stool specimens were collected from 506 children under 5 years of age hospitalized with acute diarrhoea (289 male and 208 female), and human astrovirus was investigated by RT-PCR. Associations of socio-demographic, clinical, and behavioural conditions with infection were analysed. Results: The overall prevalence of human astrovirus was found to be 10.3%. The mean age of positive cases was 12.41 ± 6.21 months and this was associated with infection ( p  = 0.013). Children >18 months of age were at three times the risk of infection when compared to those aged 0–6 months (odds ratio (OR) 3.19, 95% confidence interval (CI) 1.15–8.88; p  = 0.026). Children living in houses with more than one room (OR 0.60, 95% CI 0.28–0.96; p  = 0.036) and mothers using treated water (OR 0.47, 95% CI 0.25–0.86; p  = 0.015) were associated with reduced infection. Conclusions: In this study, infection with astrovirus was common in acute gastroenteritis cases among children younger than 5 years of age. Drinking treated water and living in non-crowded environments protected the children from infection.